# Calculus

Differentiate

ln(cos(2x))

1. just use the chain rule

d/dx ln(u) = 1/u du/dx

d/dx ln(cos(2x)) = 1/cos(2x) (-2sin(2x)) = -2tan(2x)

posted by Steve
2. 3\4 3\1 3\6

posted by Ms.Vargas

## Similar Questions

1. ### trigo help!

1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)
2. ### calculus

Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x)
3. ### Calc.

Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x)
4. ### Mathematics

How would I differentiate y = 4cos(2x)cos(3x) u = cos(2x) u' = -2sin(2x) v = cos(3x) v' = -3sin(3x) This is all I have so far
5. ### differentiate

differentiate cos^2x dx tnk u
6. ### Integral calculus

Please can anyone help with the following problems - thanks. 1) Integrate X^4 e^x dx 2) Integrate Cos^5(x) dx 3) Integrate Cos^n(x) dx 4) Integrate e^(ax)Sinbx dx 5) Integrate 5xCos3x dx The standard way to solve most of these
7. ### Calculus

I think I have the correct answers for the following problems. For anyone who has the time I would appreciate it if you could tell me if I am correct/incorrect. Thank you. 1). Differentiate ã(x)sin x = (2xcosx+sinx)/2ã(x)
8. ### Calculus

How do you differentiate sin^2(cos t) My work: =2sin(cos)(cost)(-sint)
9. ### Math

Differentiate ln (1+ cos x)... My ans is (-sin x)/ (1+cos x), but at wolfram is -tan (x/2). I think they simplify it but how did they do it? Sorry for my little knowlegde....
10. ### Calculus

Differentiate. e^cos(x^2+1) Is the answer -2xe^cos(x^2+1) sin(x^2+1)?
11. ### Calculus

Differentiate e^cos (x^2+1). My answer: -2xe^cos(x^2 +1) • sin(x^2+1)

More Similar Questions